PERCEPTIONS OF HIGH SCHOOL TEACHERS IN PALU CITY TOWARDS DIFFERENTIATED LEARNING - Putu Satya Narayanti; Lilies Tangge, Afadil (International Journal of Teaching and Learning, 2024)
Differentiated learning is an approach that adapts to the learning needs of each student. Teachers provide facilities that suit students' individual needs, bearing in mind that each student has unique characteristics and cannot be treated uniformly. This article aims to provide a deeper understanding of learning differentiation and explore teachers' perceptions regarding its implementation in the classroom. The results of interview research show that the purpose of differentiated learning is to coordinate learning by paying attention to students' interests, readiness and learning preferences. This aims to help all students achieve learning goals, increase motivation and learning outcomes, and establish a harmonious relationship between teachers and students, so that students are more enthusiastic about learning. In conclusion, differentiated learning gives students the opportunity to learn naturally and efficiently with the help of teachers who are able to combine the required methods and approaches. There are several obstacles that arise, such as limited facilities and infrastructure that support the differentiated learning process, teachers need time to prepare learning instruments, appropriate methods and appropriate media, implementing differentiated learning requires relatively high costs and teachers must have good classroom management skills.